2012
DOI: 10.1590/s1516-44462012000200011
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and higher rates of psychiatric re-hospitalization: São Paulo public mental health system

Abstract: Family's stigma towards mental illness might contribute to the increase in readmission rates of their relatives with psychiatric disorders. More studies should be conducted to depict mechanisms by which stigma increases re-hospitalization rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 35 publications
1
29
1
4
Order By: Relevance
“…Recent studies observed that early readmission rates, usually defined as occurring within 90 days of discharge, can be as high as 13% 11. Several factors were associated with readmission, but number of previous admissions seemed to be one of the most important predictors of readmission 7. This would fit with the theory of “revolving-door” patients 12.…”
Section: Negative Outcomes After Discharge From a Brief Psychiatric Hmentioning
confidence: 72%
See 3 more Smart Citations
“…Recent studies observed that early readmission rates, usually defined as occurring within 90 days of discharge, can be as high as 13% 11. Several factors were associated with readmission, but number of previous admissions seemed to be one of the most important predictors of readmission 7. This would fit with the theory of “revolving-door” patients 12.…”
Section: Negative Outcomes After Discharge From a Brief Psychiatric Hmentioning
confidence: 72%
“…A Brazilian study, conducted in São Paulo, the most populous metropolis of the country, also assessed rehospitalization rates among patients with psychotic and bipolar disorders. After 1 year of follow-up, the readmission rate of the sample was 43% 7. In the US 150 patients discharged from a psychiatric ward were also followed up for 1 year.…”
Section: Negative Outcomes After Discharge From a Brief Psychiatric Hmentioning
confidence: 99%
See 2 more Smart Citations
“…No Brasil, há poucos estudos que avaliam as atitudes de profissionais de saúde mental com relação aos indivíduos com transtornos mentais. Loch 12 pesquisaram as atitudes dos psiquiatras para com esquizofrênicos no Congresso Brasileiro de Psiquiatria (2009) em São Paulo. Para tanto, utilizaram um questionário que avaliava estereótipos negativos, opinião sobre psicotrópicos e tolerância aos efeitos colaterais.…”
Section: ▄ Introduçãounclassified